HAK ASASI MANUSIA DAN TANTANGAN KECERDASAN ARTIFISIAL (ARTIFICIAL INTELLIGENCE) DALAM KEAMANAN SIBER GLOBAL - Nungki Sundias (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
The development of Artificial Intelligence (AI) in the field of global cybersecurity presents a significant legal paradox: the tension between the necessity of national security protection and the obligation to respect Human Rights. While the utilization of AI for digital surveillance, cyber threat detection, and large-scale data analysis enhances security effectiveness, it simultaneously risks infringing upon the right to privacy, freedom of expression, the principle of non-discrimination, and state accountability. These challenges are further complicated within the ASEAN region and an international legal order that remains fragmented. This research aims to analyze the challenges of human rights protection in AI utilization for global cybersecurity through a comparative perspective of ASEAN national laws and international law. The research employs a normative juridical method with conceptual, statutory, and comparative approaches, examining national regulations in several ASEAN countries alongside international legal instruments related to human rights, cybersecurity, and AI governance. The findings indicate that AI regulation in cybersecurity across ASEAN countries remains predominantly security-oriented and has not fully adopted a human rights paradigm. At the international level, the absence of binding legal instruments results in weak standards for human rights protection in AI practices. This study asserts a philosophical novelty in the form of a paradigm shift from state security-centric governance toward a human-centered and rights-based governance of AI. The research recommends the harmonization of ASEAN regulations and the strengthening of human rights-based international norms in the governance of AI and global cybersecurity.